Pengaruh profitabilitas, leverage dan ukuran perusahaan terhadap nilai perusahaan - Harianto, Ricky; Hendrani, Ai (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of profitability, leverage and firm size on firm value in the agricultural sector listed on the IDX for the 2016-2020 period. This study uses quantitative methods that aim to see the relationship between variables. The sample used in this study are agricultural sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The population is 28 companies, the sample is selected using purposive sampling method with predetermined criteria so that 7 companies can be collected with a total of 42 financial statements. The type of data is secondary data sourced from financial reports and annual reports. The data analysis method used is the Normality Test, Classical Assumption Test, Multiple Linear Regression Test, t-test, f-test and Coefficient of Determination Test (R2). The results of this study indicate that simultaneously profitability, leverage and firm size have an effect on firm value. The conclusion from the results of this study is that partially profitability has a positive effect on firm value, partially leverage has no effect on firm value and partially negative effect on firm size.